The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4049/jimmunol.1700914
|View full text |Cite
|
Sign up to set email alerts
|

A Chlamydia-Specific TCR-Transgenic Mouse Demonstrates Th1 Polyfunctionality with Enhanced Effector Function

Abstract: Chlamydia is responsible for millions of new infections annually, and current efforts focus on understanding cellular immunity for targeted vaccine development. The Chlamydia-specific CD4 T cell response is characterized by the production of IFNγ, and polyfunctional Th1 responses are associated with enhanced protection. A major limitation in studying these responses is the paucity of tools available for detection, quantification, and characterization of polyfunctional, antigen-specific T cells. We addressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 83 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…4). While this has previously been shown indirectly (8,14,15,22), our use of IFN-␥ Ϫ/Ϫ NR1 T cells confirms the importance of IFN-␥ production during C. trachomatis infection. Interestingly, IFN-␥R Ϫ/Ϫ NR1 T cells were still able to protect mice, suggesting that their ability to produce IFN-␥ was enough to help clear infection.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…4). While this has previously been shown indirectly (8,14,15,22), our use of IFN-␥ Ϫ/Ϫ NR1 T cells confirms the importance of IFN-␥ production during C. trachomatis infection. Interestingly, IFN-␥R Ϫ/Ϫ NR1 T cells were still able to protect mice, suggesting that their ability to produce IFN-␥ was enough to help clear infection.…”
Section: Discussionsupporting
confidence: 84%
“…Those studies showed that antigen-specific CD8 ϩ T cells do localize in sections of the genital tract containing LCMV, correlating with our findings with C. trachomatis. Given this, it is possible that transgenic CD8 ϩ T cells specific for C. trachomatis protein CrpA (7) or transgenic CD4 ϩ T cells corresponding to C. muridarum (8) would similarly be able to home to the specific sites within the genital tract that contain bacteria. Future work will address whether or not this is an NR1 or transcervical inoculation-specific phenomenon within the context of Chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that establishment of resident T cells from T cells originating from circulation may not be strictly dependent on neither α4 or CD103, but does involve CD69 in agreement with previous studies on CD4 Trm cells in various tissues 46 including the genital tract. 47 Interestingly, our data showed that inhibiting lymphocyte egress from the lymph nodes, including the infectiondraining lymph nodes, resulting in a strong decline in T cell numbers in blood, did not reduce the expansion of T cells in the GT or compromize the protection. This showed that in the first phase of the infection, the Trm cells were sufficient to induce a protective immune response ( Fig.…”
Section: Discussionmentioning
confidence: 66%